A Combined Model for Continuous Intention to Use E-Learning System - Tawafak R.M.; Malik S.I.; Mathew R.; Ashfaque M.W.; Jabbar J.; AlNuaimi M.N.; ElDow A.; Alfarsi G. (International Association of Online Engineering, 2023)
E-learning systems installed in educational institutions have increased the efficiency of educational processes over the years. E-learning, however, has faced many factors affecting the continuous intention of teachers and students to use e-learning, such as student satisfaction, productivity, and academic success. Therefore to improve academic success, there is a need for institutions to enhance their e-learning programs. Thus the primary objective of this thesis is to construct a composite. This research focuses on advancing e-learning to boost students continuous trying to use e-learning to increase students understanding and academic performance. Data were collected using questionnaires returned to determine their e-learning feedback by 295 undergraduates from four universities in Oman, after which (PLS-SEM) used e-learning to assess their ongoing trial of using e-learning. The facts demonstrate that the variables are essential for the continuing decision to use e-learning. 2021. All Rights Reserved.